Effect of Melatonin on Paclitaxel-Associated Acute and Chronic Pain: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Naeeme Talaee; Sholeh Ebrahimpour; Mohsen Sfandbod; Hossein Majedi; Aarefeh Jafarzadeh Kohneloo; Kheirollah Gholami; Zahra Jahangard-Rafsanjani (Tabriz University of Medical Sciences, 2022)
Background: Taxane-induced pain is a disabling condition. This trial was conducted to assess the effects of melatonin on preventing paclitaxel-associated acute and chronic pain or decreasing its severity in patients with breast cancer. Methods: This randomized, double-blind, placebo-controlled clinical trial was conducted on breast cancer women who received weekly paclitaxel (80 mg/m2) with or without trastuzumab after using doxorubicin + cyclophosphamide. The intervention group randomly received oral melatonin (10 mg/day) or placebo, which started from the first night of chemotherapy and continued through the planned 12 weeks of chemotherapy. The level of arthralgia-myalgia as acute pain was assessed every day in both groups using the Brief Pain Inventory (BPI). The Douleur Neuropathique 4 questionnaire (DN4) and National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE) version 5.0 were used to measure chemotherapy-induced peripheral neuropathy as chronic pain. Results: Seventeen patients were enrolled in each group randomly. The incidence of neuropathy according to a DN4 score ≥ 4 was significantly lower in the melatonin group versus the placebo group at week 12 compared to baseline (5 vs 11, P-value= 0.039). In addition, the mean neuropathy severity was significantly lower in the melatonin group over time (β= -0.051, P-value= 0.01). However, there were no significant differences in the mean worst and least pain scores over the twelve cycles of treatment between arms (P-value= 0.633 and 0.34, respectively). Conclusion: Co-administration of melatonin in women with breast cancer decreased the incidence of severe paclitaxel-associated neuropathy but melatonin was not effective against acute pain.